PROTECTION OF ENVIRONMENT DURING ARMED CONFLICTS IN INTERNATIONAL LAW: QUALIFICATION OF DAMAGE AND RESPONSIBILITY - Nurullayev, Ilkin (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Aim of the article: the article is devoted to a comprehensive study of international legal mechanisms for environmental protection during armed conflicts and to the issues of international criminal responsibility for environmental damage. The relevance of the topic is determined by the large-scale and long-term environmental consequences of modern wars, in particular the armed aggression of the russian federation against Ukraine, which is accompanied by the destruction of ecosystems, pollution of natural resources, and the creation of risks to environmental security at both regional and global levels. Methods: the methodological basis of the study consists of a combination of general scientific and specialised legal methods, the application of which has enabled a comprehensive analysis of international legal mechanisms for the protection of the environment during armed conflicts: the dialectical method, the formal-legal (dogmatic) method were used to analyse the content of international legal norms, in particular the provisions of Additional Protocol I to the Geneva Conventions, the Rome Statute of the International Criminal Court and the ENMOD Convention, as well as to establish the legal elements of a war crime involving damage to the environment. Results: the study further explores contemporary international initiatives aimed at criminalizing ecocide as a potential standalone international crime and assesses their significance for expanding the scope of international responsibility for large-scale environmental destruction beyond the context of armed conflict. It substantiates the possibility of enhancing the effectiveness of existing mechanisms through a more inclusive and systematic interpretation of current norms of international humanitarian and international criminal law, taking into account modern scientific knowledge of ecological processes and the cumulative nature of environmental harm. Discussion: the article concludes that it is necessary to strengthen international legal instruments for ensuring responsibility and securing compensation for environmental damage caused by armed aggression, which is essential for environmental restoration and for reinforcing the preventive function of international law.